2022
DOI: 10.1097/j.jcrs.0000000000001054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anatomical differences and intraocular lens design on negative dysphotopsia

Abstract: Ray-tracing simulations show that anatomical differences between patients with and without negative dysphotopsia have a strong, up to 18%, effect on the severity of the complaint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…11 All simulations were performed in OpticStudio (v. 20.3.2, Zemax, LCC) through the ZOSPy package (v. 0.6.1). 6,20 A wavelength of 543 nm and corresponding refractive indices were used. 11 Two different IOL designs were used for the pseudophakic eye model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 All simulations were performed in OpticStudio (v. 20.3.2, Zemax, LCC) through the ZOSPy package (v. 0.6.1). 6,20 A wavelength of 543 nm and corresponding refractive indices were used. 11 Two different IOL designs were used for the pseudophakic eye model.…”
Section: Methodsmentioning
confidence: 99%
“…For each ray, the location where it illuminated the retina was determined, which was expressed as the angle with respect to the center of the retina (Figure 1). 6 The relation between the visual field angle and the illuminated retinal location in the phakic eye model was used as a reference to determine whether exchanging the crystalline lens for an IOL would induce a shift in the visual field. To that end, the illuminated retinal locations of the pseudophakic eye were mapped onto the illuminated retinal locations of the phakic eye.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, van Vught et al performed quantitative measurements, similar to those of Fernández et al, in a cohort of ND patients and showed that they have larger deviations from a textbook eye model than controls [4]. Later studies subsequently confirmed that these anatomical differences have a direct relation with the shadow perceived by these subjects [2]. The study of Fernández provides a similar first set of clues for PD by showing that the amount of light distortion is related to the temporal centration of the IOL.…”
mentioning
confidence: 92%
“…Although ray tracing studies have unveiled the most likely optical origins of these conditions [1,2], the understanding of why specific patients perceive these complaints and others do not is still a topic of continuing research and debate. The study by Fernández et al [3] highlights two important elements, which are essential to understand the visual performance on the single subject.…”
mentioning
confidence: 99%